Validity of E-PASS Score for Evaluating Perioperative Minor Complications Associated with Carotid Endarterectomy - Yutaka MORISHIMA; Masahito KAWABORI; Yoichi ITO; Masayuki GEKKA; Koji FURUKAWA; Yoshimasa NIIYA; Miki FUJIMURA (Neurologia Medico-Chirurgica)
Carotid endarterectomy (CEA) is conducted to reduce the risk of cerebral infarction; therefore, a low complication rate is highly required. To predict long-term morbidity and mortality, various scoring systems have been considered; nonetheless, a model that can be utilized to estimate nonmajor temporary complications and minor complications is currently lacking. To evaluate the occurrence rate of perioperative complications in various surgical domains, the E-PASS (Estimation of Physiological Ability and Surgical Stress) score is employed. This study was carried out to investigate the utility of the E-PASS score as a predictive factor for the risk of minor complications in patients undergoing CEA. The retrospective analysis was performed for 104 consecutive series of CEA procedures carried out at Otaru Municipal Hospital. The correlation between E-PASS and the rate of minor complications was examined. Sensitivity and specificity were used to construct a receiver operating characteristic curve, and the area under the curve (AUC) was calculated for accuracy. Postoperative minor complications occurred in eight cases (7.7%), including six vagal nerve injuries and two pneumonia cases. Three categorical data-preoperative risk score, surgical stress scores, and comprehensive risk score (CRS)-showed a good relationship with the postoperative minor complication. Among them, CRS presented the highest sensitivity and specificity, as indicated by an AUC of 0.68. The CRS cutoff value was calculated as −0.068, with a 1.7% postoperative minor complication rate for those lower than −0.068 and 14.0% for those higher than −0.068. The E-PASS score was effective for evaluating and predicting postoperative minor complications in patients with CEA procedures.